Implementasi Strategi Customer Service Dalam Meningkatkan Kepuasan Dan Literasi Nasabah Pada Bank Syariah Indonesia KCP Stabat K.H Zainul Arifin - Muhammad Arif Haikal Lubis; Yanti, Nursantri (Fakultas Ekonomi dan Bisnis Islam IIQ An Nur Yogyakarta, 2023)
This study aims to determine customer service strategies in improving services to sharia principles, and to determine customer understanding of sharia banks. In this study the authors used a qualitative approach and type of research (field research), data collection techniques by means of interviews and documentation. Furthermore, data analysis uses the description method. The data source is Bank Syariah Indonesia KCP Stabat K.H Zainul Arifin. Based on the results of the research, it can be concluded that the strategy used by Bank Syariah Indonesia KCP Stabat K.H Zainul Arifin customer service to improve service to customers at Indonesian Islamic banks KCP Stabat K.H Zainul Arifin is service customer service in providing services to its customers, namely using the basic strategy of being friendly, responsive, and always paying attention to name tags, while the main strategy is Responsiveness, Competence, Credibility, Contribution. , Honesty (honesty), Excellent Service (excellent service), Innovation (change). Keywords: Implementation, Strategi, Costumers Servic, Literacy